Audit Firm Portfolio Management Decisions - JOHNSTONE, KARLA M.; BEDARD, JEAN C. (Journal of Accounting Research, 2004)
ABSTRACT We examine client acceptance and client continuance decisions of a large audit firm to provide empirical evidence on the extent and nature of risk avoidance that the firm uses to purposefully manage its client portfolio. Our results support several key new inferences regarding audit firm portfolio management decisions. First, the results show that this firm is shedding the riskier clients in its portfolio, consistent with the risk avoidance theory of audit firm portfolio management. Second, the results show that the firm's newly accepted clients are less risky than its continuing clients. Although results of both the client continuance and client acceptance decisions imply a less risky portfolio emerging over time, there are greater differences in risk between continuing and discontinued clients than between continuing and newly accepted clients. Third, we find that audit risk factors are more important in audit firm portfolio management decisions than are financial risk factors. Finally, we find no evidence that audit pricing affects the client acceptance and continuance decisions of this firm, controlling for risk and other client characteristics.